Obesity is associated with a higher prevalence of musculoskeletal pain in middle-aged women. (4th May 2017) - Blümel, Juan Enrique; Arteaga, Eugenio; Mezones-Holguín, Edward; Zúñiga, María Cristina; Witis, Silvina; Vallejo, María Soledad; Tserotas, Konstantino; Sánchez, Hugo; Onatra, William; Ojeda, Eliana; Mostajo, Desiree; Monterrosa, Alvaro; et al.
Abstract: Musculoskeletal pain (MSP) has been recently linked with high plasma leptin levels. Our objective was to study if obese women, who have higher leptin levels, could have a higher frequency of MSP. We studied 6079 Latin-American women, 40–59 years old. Their epidemiological data were recorded and the Menopause Rating Scale (MRS), Golberg Anxiety and Depression Scale and Insomnia Scale were applied. MSP was defined as a score ≥2 on MRS11. Women with MSP were slightly older, had fewer years of schooling and were more sedentary. They also complained of more severe menopausal symptoms (29.2% versus. 4.4%, p  < 0.0001). Furthermore, they had a higher abdominal perimeter (87.2 ± 12.0 cm versus 84.6 ± 11.6 cm, p  < 0.0001) and a higher prevalence of obesity (23.1% versus 15.2%, p  < 0.0001). Compared to normal weight women, those with low body weight (IMC <18.5) showed a lower risk of MSP (OR 0.71; 95%CI, 0.42–1.17), overweight women had a higher risk (OR 1.64; 95%CI, 1.44–1.87) and obese women the highest risk (OR 2.06; 95%CI, 1.76–2.40). Logistic regression analysis showed that obesity is independently associated to MSP (OR 1.34; 95%CI, 1.16–1.55). We conclude that obesity is one identifiable risk factor for MSP in middle-aged women.